Instrument for the control and evaluation of the tactical technical performance in the baseball pitchers - Rogelio García Morejón; Victor Oreste Cordero Valdés (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The control and evaluation of the tactical technical action in the training in game situations, is an aspect that is made difficult by the lack of definition of indicators to be taken into account in baseball, specifically in the pitching area. Therefore, the objective of this article focuses on proposing an instrument for the control and evaluation of the tactical technical performance of baseball pitchers, category 15-16, in game situations, during the training unit, as well as in sports competition. For this purpose, we worked with a primary sample of 15 pitchers of the 15-16 years old category of the Sports Initiation School, "Ormani Arenado Llonch" of Pinar del Río and nine coaches as a secondary sample. Scientific research methods and techniques were used, such as document analysis, observation, standardized and individual interviews. Shortcomings were found in the treatment of the control and evaluation of the tactical technical preparation, in terms of the baseball pitcher's tactical technical action in game situations based on the creation of an instrument that provided the coach with information about the state of the pitcher's tactical technical action, by promoting the treatment of weaknesses presented by the athletes in this game area.